Macroeconomic Legal Trends in the EU11 Countries - Vértesy, László (Public Governance, Administration and Finances Law Review, 2018)
This contribution deals with the macroeconomic legal trends in the Eastern member states of the European Union, so called EU11: Bulgaria, Croatia, the Czech Republic, Estonia, Latvia, Lithuania, Hungary, Poland, Romania, Slovakia and Slovenia. The paper discusses the development from the 1990s to nowadays, emphasizing the initial changes and the consolidation after the financial crisis. Therefore, the fiscal policy bears a major attention: fiscal and budgetary stability, government debts, fiscal controls (auditing and independent fiscal councils), for a more comprehensive overview, some ports of the monetary policy will be examined: national banks and price stability. The main aim of the contribution is to confirm or disprove the hypothesis that there is any identifiable or verifiable correlation between the legislation and the macroeconomic trends: sustainable balanced budget and government debt, economic growth, inflation. The research is based on law and economics, especially law and finance methodology with quantitative analysis, because of the cross-discipline nature of the topic. The paper contains some comparative statistics to evaluate the certain results upon figures, because it is even important to match the legal provisions with the economic performance.